Heterologous Expression and Purification of ? Galactosidase Protein Using Affinity Chromatography - Alam, M. Z.; Ragionieri, L.; Santos, M. A. S.; Iqbal, A. (Journal of Scientific Research, 2013)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --><!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> <![endif]--> Enzymes and other protein purification using recombinant DNA technology have become popular due to scarcity of natural protein. Saccharomyces cerevisiae is a demanding host, since it facilitates protein expression by its relative simplicity, safe organisms, inexpensive and has many properties of eukaryotic expression system. As an alternative host we express E. coli lacZ gene with GST tag in Saccharomyces cerevisiae and successfully purified from soluble extracts. The concentration of soluble GST-? galactosidase protein was approximately 0.57 mg/ml of elution buffer yielded from 50 ml yeast cell culture. The ?-galactosidase protein from insoluble extract was low due to the increasing solubility of GST tag. Keywords: ?-galactosidase; Heterologous expression; GST tag; Affinity chromatography. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i3.13820 J. Sci. Res. 5 (3), 499-513 (2013)